2013
DOI: 10.1002/stem.1312
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Abundance of Apurinic/Apyrimidinic Endonuclease Causes Failure of Base Excision Repair in Culture-Adapted Human Embryonic Stem Cells

Abstract: The inevitable accumulation of chromosomal abnormalities in human embryonic stem cells (hESCs) during in vitro expansion represents a considerable obstacle for cell replacement therapies. To determine the source of chromosomal abnormalities, we examined hESCs maintained in culture for over 55 months for defects in telomere maintenance and DNA repair. Although prolonged culture affected neither telomerase activity nor nonhomologous end joining, the efficiency of base excision repair (BER) was significantly decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…of decreases in DNA maintenance associated with long-term cultivation [30] or whether other mechanisms projected to increase MF and the high MF-associated mutations are the reason for the DNA maintenance decrease in hESCs. Considering that similar effects of increases in MF up to 50% were achieved with the inhibition of APE1 in hESCs (MOX or anti-APE1 siRNA; Figs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…of decreases in DNA maintenance associated with long-term cultivation [30] or whether other mechanisms projected to increase MF and the high MF-associated mutations are the reason for the DNA maintenance decrease in hESCs. Considering that similar effects of increases in MF up to 50% were achieved with the inhibition of APE1 in hESCs (MOX or anti-APE1 siRNA; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BER appears to be important not only for the amelioration of base damage but also to trigger checkpoint control mechanisms by releasing double-stranded breaks as BER-mediated clustered damage repair intermediates [30]. Thus, BER failure not only increases the base damage burden but also renders checkpoints less sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A mechanism involving the down-regulation of Apurinic Endonuclease 1 (APE1) and subsequent failure of BER has been described to explain this phenomenon in cultured human ESCs [105]. The authors reported that a decrease in the efficiency of the BER pathway meant that oxidative base damage was not converted by glycosylases to DNA DSBs [106;107] and therefore caused an accumulation of damage.…”
Section: /31mentioning
confidence: 99%